The Influence of Social Norms on Debt Behavior, With Intervention in Debt as an Intervening Variable - Santoso, Aprih; Sulistyawati, Ardiani Ika (Jurnal Mamangan, 2023)
The main problem of this research is whether interest can play a role in mediating social norms in one's behavior. The research objective was to examine the influence of social norms on indebtedness behavior in the Semarangan batik UMKM community, with interest in debt as a mediating variable. The theory used in this research is the TPB theory. The research method is: the population of all Semarangan batik UKM community entrepreneurs who owe Wibawa credit in the city of Semarang is 197 people and is also used as a research sample (census method). Data analysis method with the AMOS-25 program. The results showed that social norms had a positive and significant effect on interest, and social norms, interest in debt also had a positive and significant effect on debt behavior in the Semarangan batik UMKM community. The conclusion is that interest in debt is able to mediate the influence of social norms on debt behavior in the Semarangan batik UMKM community. The novelty of this research is the use of TPB theory in this social research, because so far TPB theory has been widely used in psychological research.